Old, not odd: Running laches against the states and the future of antitrust after 'New York v. Meta Platforms' - Schulze, Frank (Michigan law review, 2024)
In 'New York v Meta Platforms, Inc' the United States Court of Appeals for the D.C. Circuit applied equitable laches to an antitrust lawsuit brought by 46 state attorneys general, holding that they had not brought their claims in their role as law enforcers. 'Meta Platforms' is the latest in a line of cases that has characterized antitrust actions by state attorneys general as non-public and non-governmental. But this characterization is in tension with the historical role of state attorneys general in enforcing the antitrust laws and undermines the original design of the federal antitrust statutes as supplements to state enforcement activities. This note argues that state antitrust enforcement is an insurance policy against federal underenforcement and a mechanism to reflect the popular will. The 'Meta Platforms' decision observed that the status of the states as plaintiffs independently factors into the court's laches analysis. This observation - which this note calls "the states factor" - suggests that all else equal, a suit brought by the states to vindicate a quasi-sovereign interest on behalf of its citizens is less likely to be stale than a similar one from a purely private actor. If courts afford limited weight to the "states factor" and run laches against elected antitrust enforcers, they make the federal statutes less efficient for their original purpose of supplementing state enforcement activity.